2004
DOI: 10.1104/pp.104.041467
|View full text |Cite
|
Sign up to set email alerts
|

Activity Profiling of Papain-Like Cysteine Proteases in Plants

Abstract: Transcriptomic and proteomic technologies are generating a wealth of data that are frequently used by scientists to predict the function of proteins based on their expression or presence. However, activity of many proteins, such as transcription factors, kinases, and proteases, depends on posttranslational modifications that frequently are not detected by these technologies. Therefore, to monitor activity of proteases rather than their abundance, we introduce protease activity profiling in plants. This technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
130
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 33 publications
(35 reference statements)
10
130
0
10
Order By: Relevance
“…Little is known about the physiological functions of these peptidase. In plants, for example, they have been associated with the mobilization of nutrients and defence against pathogens [3,28,47]. Many of these enzymes have important applications in medicine and biotechnology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the physiological functions of these peptidase. In plants, for example, they have been associated with the mobilization of nutrients and defence against pathogens [3,28,47]. Many of these enzymes have important applications in medicine and biotechnology.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are usually synthesized as inactive or less active precursors. Activation takes place by limited intra-or intermolecular proteolysis [3]. To date, the amino acid sequences of more than 50 papain-like and 15 legumain-like plant proteinases have been established [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pellets were dissolved in SDS gel loading buffer. Detection of biotinylated proteins was done as described previously using streptavidin-HRP polymer (Sigma-Aldrich; van der Hoorn et al, 2004).…”
Section: Inhibition Assays With Agroinfiltrated Proteasesmentioning
confidence: 99%
“…1 A, b). Protein sequencing and immunoprecipitation studies identified RD21, a PLCP previously identified by DCG-04 activity profiling (25), in protein extracts of 4.5-d-old etiolated seedlings ( Fig. 1 A, a, lane 3 vs. lane 2, product C1).…”
Section: Resultsmentioning
confidence: 99%